2016 General Elections: Vote 4 Education, Vote 4 Health - Nabwowe, Angella; Mncwabe, Nokukhanya (My University, 2015)
70 Year old Zaina Bakanansa, resident of Kyetume-Bukasa village, Nakisunga Sub- County Mukono District believes elections are just a waste of time. “ No Member of Parliament or Local Council Chairperson has made a difference in my life”, she says. Bakanansa’s need is to have a health facility in her village “ I am weak and sickly and unfortunately I cannot access a health facility. The private clinic close to my house is too expensive for me”. The Mukono Health centre IV or Nazigo health centre III which are public health facilities are quite a distance from her house, several kilometres away. Her only hope would be in voting leaders with a manifesto that addresses her concerns but she has been disappointed many times. “I have participated in national elections but I don’t see the benefits. When I have health needs , I call on a Non- Governmental Organisation to get help and they are always responsive.” The Constitution of the Republic of Uganda gives citizens like Zaina Bakanansa power, to elect the political leaders of the country every after five years. Very soon, Ugandans shall elect political leaders – from the local level to the President.